Rancang Bangun Alat Pengamatan Gas Radon Menggunakan RN53 STK - Adji Satrio; Hariyanto; Agustya Adi Martha; Wandes Gumamven (Syntax Literate, 2023)
Radon (Rn222) is a radioactive element derived from Uranium (U238) which emits alpha particles in its decay process. Detection of radon gas is important because it is not harmful to health. Besides being harmful to health, radon detection is also carried out to determine changes in radon gas related to seismic activity. The Meteorology, Climatology, and Geophysics Agency (BMKG) conducts observations of radon gas concentrations to determine changes in seismic activity. The design of the radon gas measurement instrument using the RN53 sensor is to monitor radon gas concentrations at the location and can be sent via the GSM network to the Thingspeak platform. The design of this instrument using the RN53 sensor has a correction of -92.90 Bq/m3, so it is necessary to make adjustments as well as calibration and comparisons again. The observations from the system are displayed on the LCD, stored on the microSD, and sent to Thingspeak.